Controle alternativo da pinta preta do inhame (Dioscorea sp.) - Carvalho, Valdeir Nunes (2019)
The black spot of the yam (Curvularia eragrostidis (Henn.) Meyer) causes economic disturbances to the producers of the yam crop (Dioscorea spp.). The implementation of a control alternative can contribute to the solution of the problem. The objective of this work was to evaluate the ability of the natural products and inducers of resistance in the control of black spot yam. Bioassays were carried out in greenhouse (preventive and curative), to which the treatments were evaluated: mint oil (100μL); garlic extract (20%), yam extract (20%); Trichoderma sp. (2.0 g L-1); ASM (0,15 g L-1 and 0.3 g L-1); Ecolife® (2%); mancozeb (1.7 g L-1) and water (control), applied on the leaves of yam plants, 48h and 72h before and after inoculation of the pathogen (1,7 x 106 con.mL-1). Two field experiments were carry out. The first experiment prepared beds containing Bioplant planting substrate, followed by the planting of yams rhizophores cv. Da Costa. Two and four days after the onset of disease symptoms (natural infection), the plants were sprayed with 10mL of the treatments, selected in the previous experiment: mint oil (100μL), garlic leaf extracts (20%), yam leaf extracts (20%), Trichoderma sp. (2.0 g L-1), ASM (0.3 g L-1) and mancozeb (1.7 g L-1). The Tween 20 patch (1mL) was added to all treatments. Disease severity was assessed fifteen days after the treatments. In the second, it was carried out the planting of the rhizophores of yam cv. Da Costa, following the same conditions of the previous test. The treatments used came from the best evaluations of previous experiments: the fungus Trichoderma sp. (2.0 g L -1); garlic extract (20% v / v); ASM (0.3 g L -1); the fungicide mancozeb (1.7 g L -1), at 48 h and 72 h after symptom onset. The control was treated with ADE alone. Tween 20 (1mL) patch was added to all treatments. The evaluations were performed the fifteen days and 30 days after the onset of symptoms. Later, 45-day old yams were treated with Trichoderma sp. (48h and 72h); minty oil and clove oil. The plants were inoculated 24 hours after treatment, and the activity of the enzymes Peroxidases (POX) and Phenylalanine Ammonia-Liase (PAL) related to plant defense responses, were performed after 24, 48, 72 and 96 hours. The data were submitted to analysis of variance (ANOVA) and the means were compared by the Tukey test at the 5% probability level. The results showed that treatments with Yam leaf extract, Trichoderma sp. fungus, mint oil and mancozeb applied up to 72h prior to inoculation of the pathogen, reduced the severity of the black yarn spot. Mancozeb applied 48h and 72h, Trichoderma sp. and mint oil applied 48h after inoculation of the pathogen, were efficient in controlling the disease under greenhouse conditions and reduced the severity of the disease under field conditions. The fungus Trichoderma sp. persisted in the area 30 days after its application and induced the resistance of yam plants, activating Phenylalanine ammonia (FAL) and Peroxidase of phenols (POX). It can be concluded that the fungus Trichoderma sp. (2.0 g L -1), applied preventively or curatively, is able to control the black dye of the yam.